Detection of subtle left ventricular systolic dysfunction in patients with significant aortic regurgitation and preserved left ventricular ejection fraction: speckle tracking echocardiographic analysis. (2nd March 2015) - Ewe, See Hooi; Haeck, Marlieke L.A.; Ng, Arnold C.T.; Witkowski, Tomasz G.; Auger, Dominique; Leong, Darryl P.; Abate, Elena; Ajmone Marsan, Nina; Holman, Eduard R.; Schalij, Martin J.; Bax, Jeroen J.; Delgado, Victoria
Abstract: Aims: The aim of this study was to characterize left ventricular (LV) mechanics in symptomatic and asymptomatic patients with moderate-to-severe or severe aortic regurgitation (AR) and preserved ejection fraction (left ventricular ejection fraction) using two-dimensional speckle tracking echocardiography (2D-STE). The association between baseline LV strain and development of indications for surgery in asymptomatic patients was also evaluated. Methods and results: A total of 129 patients with moderate-to-severe or severe AR and LVEF >50% (age 55 ± 17 years, 64% male, 53% asymptomatic at baseline) were included. Standard echocardiography and 2D-STE were performed at baseline. Compared with asymptomatic patients, symptomatic patients had significantly impaired LV longitudinal (−14.9 ± 3.0 vs. −16.8 ± 2.5%, P < 0.001), circumferential (−17.5 ± 2.9 vs. −19.3 ± 2.8%, P = 0.001), and radial (35.7 ± 12.2 vs. 43.1 ± 14.7%, P = 0.004) strains. Among 49 asymptomatic patients who were followed up, 26 developed indications for surgery (symptoms onset or LVEF ≤50%). These patients had comparable LV volumes, LVEF, and colour Doppler assessments of AR jet at baseline, but more impaired LV longitudinal ( P = 0.009) and circumferential ( P = 0.017) strains compared with patients who remained asymptomatic. Impaired baseline LV longitudinal (per 1% decrease, HR = 1.21, P = 0.04) or circumferential (per 1% decrease, HR = 1.22, P = 0.04) strain was independently associated with the need for surgery. Conclusion: Multidirectional LV strain was more impaired in symptomatic than in asymptomatic patients with moderate-to-severe or severe AR, despite preserved LVEF. In asymptomatic AR patients, longitudinal and circumferential strains identified patients who would require surgery during follow-up.